Evaluation of two counseling strategies improving exclusive breastfeeding among HIV-negative mothers in Kibera Slum, Nairobi, Kenya : a randomized controlled trial - Ochola, Sophie Atieno (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.